Characterization of sound enamel and natural white spot lesions - Araujo, Erika Michele dos Santos; Vidal , Cristina de Mattos Pimenta; Freitas , Anderson Zanardi de; Wetter , Niklaus Ursus; Matos, Adriana Bona (Brazilian Dental Science, 2022)
Objective: To compare optical, morphological, chemical, and physical aspects of the sound enamel and whitespot lesions (WSL) classified as ICDAS 2. Material and Methods: Seventeen human molars with one surfacepresenting WSL and a sound surface (2 x 2 mm window) were characterized by Quantitative light-inducedfluorescence (QLF®), Optical coherence tomography (OCT), microhardness, and Raman spectroscopy. The ANOVAand Tukey’s test were used at 5% significance level. Results: The QLF comparison between distinct substratesyielded decreased Q (integrated fluorescence loss) of -15,37%mm2 and -11,68% F (fluorescence loss) forWSL. The OCT detected mean lesion depth of 174,43 um. ANOVA could not detect differences in the opticalattenuation coefficient between the substrates (p>0.05). Lower microhardness measures were observed in WSLthan on sound enamel (p